Calcium currents in rat thalamocortical relay neurones: kinetic properties of the transient, low-threshold current. - Coulter, D A (1989)
1. Calcium currents were recorded with whole-cell voltage-clamp procedures in relay neurones of the rat thalamus which had been acutely isolated by an enzymatic dissociation procedure. 2. Low-threshold and high-threshold Ca2+ currents were elicited by depolarizing voltage steps from holding potentials more negative than -60 mV. A transient current, analogous to the T-current in sensory neurones, was activated at low threshold near -65 mV and was completely inactivating at command steps up to -35 mV. Voltage steps to more depolarized levels activated a high-threshold current that inactivated slowly and incompletely during a 200 ms step depolarization. 3. The high-threshold current contained both non-inactivating and slowly inactivating components which were insensitive and sensitive to holding potential, respectively. 4. A 'T-type' current was prominent in relay neurones, in both absolute terms (350 pA peak current average) and in relation to high-threshold currents. The average ratio of maximum transient to maximum sustained current was greater than 2. 5. T-current could be modelled in a manner analogous to that employed for the fast Na+ current underlying action potential generation, using the m3h format. The rate of activation of T-current was voltage dependent, with a time constant (tau m) varying between 8 and 2 ms at command potentials of -60 to -10 mV at 23 degrees C. The rate of inactivation was also voltage dependent, and the time constant tau h varied between 50 and 20 ms over the same voltage range. With command potentials more positive than -35 mV, the inactivation of Ca2+ current could no longer be fitted by a single exponential. 6. Steady-state inactivation of T-current could be well fitted by a Boltzman equation with slope factor of 6.3 and half-inactivated voltage of -83.5 mV. 7. Recovery from inactivation of T-current was not exponential. The major component of recovery (70-80% of total) was not very voltage sensitive at potentials more negative than -90 mV, with tau r of 251 ms at -92 mV and 23 degrees C, compared to 225 ms at -112 mV. A smaller, voltage-sensitive component accounted for the remainder of recovery. 8. All kinetic properties, including rates of activation, inactivation, and recovery from inactivation, as well as the amplitude of T-current, were temperature sensitive with Q10 (temperature coefficient) values of greater than 2.5.(ABSTRACT TRUNCATED AT 400 WORDS)